Tencent Holdings Limited : an IPO case study - De Wet, Dario (School of Management Studies, 2015)
The purpose of this case study is to empirically investigate the phenomenon of initial public offerings (IPOs) by applying it to Tencent Holdings Limited (Tencent). Tencent is a Chinese internet and telecommunications value-added service provider that launched its IPO on 16 June 2004. Tencent is China’s largest internet firm and Asia’s most valuable brand, boasting a current market capitalization of HK$1.224 trillion (US$157.9 billion). The origins of Tencent’s success story trace back to its IPO decision, an important topic in the field of finance. The aim of this study is to investigate the structure of Tencent’s IPO, its listing decision and determining an intrinsic value of its IPO shares on its listing date. It was found that Tencent’s IPO extensively relates to academic literature surrounding IPO under-pricing and valuing unlisted companies. The results reveal that Tencent left money on the table by underpricing its offer shares and exercised its over-allotment option as a form of price stabilization. It was further found that Tencent’s underpricing was not influenced by competitor IPOs but rather by stringent IPO allotment policies and other signals of firm quality. It was also discovered that there might have been bias in the allocation of Tencent’s shares. An investigation into Tencent’s listing on the Hong Kong Stock Exchange (HKEx) revealed that while its competitors listed on the NASDAQ Stock Market, there was a clear correlation between Tencent’s operations and corporate structure to the HKEx listing and regulatory requirements. The decisive factors included domiciling in the British Virgin Island and Cayman Islands, the cost of listing on the HKEx Main Board versus the NASDAQ National Market as well as the effects of US GAAP and the Sarbanes-Oxley Act of 2002. The study was concluded with the application of a relative valuation and discounted cash flow (DCF) valuation. The relative valuation estimated a price range of HK$14.40-HK$18.72 for Tencent’s IPO shares, while the DCF estimated the intrinsic value of the shares to be HK$18.68. The analysis was comprehensive and in-depth and suggests that Tencent’s IPO shares were five times undervalued and were offered to shareholders at a deep discount.